Association Of α-Actinin With The Plasma Membrane Of Human Blood Platelets - Sixma, Jan J; Schiphorst, Marion E; Jockusch, Brigitte H (Thrombosis and Haemostasis, 1981)
The association of α-actinin with the plasma membrane of human blood platelets was investigated using immuno- adsorbed antibodies against α-actinin from porcine skeletal muscle and against actin from chicken gizzard. Platelet membranes enriched 10 times in radiolabelled wheat-germ- agglutinin were prepared utilizing the polylysine-bead technique of Cohen et al (1977). Immunofluorescent staining showed the presence of actin and α-actinin associated with these membranes.Platelets were ectolabelled with lactoperoxydase-iodina- tion. A crude membrane preparation was solubilized with Triton X 100, and incubated with anti α-actinin or appropriate control antibodies. The formed immune complexes were bound to Protein A-Sepharose beads, and subjected to 2-D- electrophoresis with i.e.f. in the first dimension, α-actinin from these membranes was not radiolabelled, had an apparent mol wt of 10U kdaltons and a pi of 6.7, similar to an α-actinin preparation from porcine skeletal muscle that was investigated in parallel. The location of α-actinin in the 2-D pattern was different from that of glycoprotein III.No specific glycoprotein was found bound to α-actinin under the experimental conditions. Treatment of membranes with non-ionic detergents and ‘protein perturbants’ indicated that α-actinin is an ‘extrinsic protein’. These data indicate that α-actinin as well as actin are closely associated with the plasma membrane, linked by electrostatic interaction. Both actin and α-actinin were not exposed on the outside in a resting platelet.